2022
DOI: 10.1186/s13052-022-01291-w
|View full text |Cite
|
Sign up to set email alerts
|

Care burden and associated factors in caregivers of children with cancer

Abstract: Background Evidence suggests that many parents who care for their children with cancer are affected by the care burden due to the chronic nature of the disease. The aim of this study was to determine the burden of care level and its related factors in the caregivers of children with cancer. Method A total of 270 caregivers of children with cancer were included in this cross-sectional study by convenience sampling method. Data collection tools were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The results of the study showed that most of the caregivers in this study were women, which was consistent with the results of other studies (20,31,32). This shows the prominent role of women in caring for cancer patients in most societies.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the study showed that most of the caregivers in this study were women, which was consistent with the results of other studies (20,31,32). This shows the prominent role of women in caring for cancer patients in most societies.…”
Section: Discussionsupporting
confidence: 92%
“…The heavy time-dependent burden can deplete the caregiver's energy and increase negative emotions [42]. The present study illustrated that parents of children with cerebral palsy tend to feel time-related pressure and restriction of their social and cultural activities due to multiple additional care tasks, which is consistent with previous studies [43,44]. The result of multiple linear regressions analysis found that the level of education, caring time, visual impairment, the degree of depression and fatigue remained statistically signi cant correlates of the caregiving burden.…”
Section: Discussionsupporting
confidence: 91%
“…Scientific advancement has led to an increase in the survival rate of children with cancer and, as a result, living with cancer affects different aspects of life of these children and their caregivers [198]. Chaghazardi et al [199] determined the level of care burden and the factors associated with it among the caregivers of children with cancer, and have highlighted that the majority of caregivers experience moderate to high care burden. Following the diagnosis, caregivers have to face several challenges such as ignorance, instability, anxiety, helplessness, confusion, and stress.…”
Section: -Diencephalic Syndromementioning
confidence: 99%